2017
DOI: 10.1177/1078155217741767
|View full text |Cite
|
Sign up to set email alerts
|

Actual versus recommended storage temperatures of oral anticancer medicines at patients’ homes

Abstract: Background Substantial quantities of unused medicines are returned by patients to the pharmacy each year. Redispensing these medicines would reduce medicinal waste and health care costs. However, it is not known if medicines are stored by patients as recommended in the product label. Inadequate storage may negatively affect the medicine and reduce clinical efficacy whilst increasing the risk for side effects. Objective To investigate the proportion of patients storing oral anticancer medicines according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Therefore, violating these storage conditions poses a serious health risk to both patients and children within households. Similarly, improper storage practices may affect the clinical efficiency of medicines in a negative manner, apart from their potential contribution towards the generation of medicinal wastes [ 42 , 43 , 44 ]. Nonetheless, close to 191 (51%) respondents agreed that they stored their medications inside medicine boxes, which is good practice as long as they are not accessible to children and the vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, violating these storage conditions poses a serious health risk to both patients and children within households. Similarly, improper storage practices may affect the clinical efficiency of medicines in a negative manner, apart from their potential contribution towards the generation of medicinal wastes [ 42 , 43 , 44 ]. Nonetheless, close to 191 (51%) respondents agreed that they stored their medications inside medicine boxes, which is good practice as long as they are not accessible to children and the vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…However, mean temperatures for the areas were much lower (18.4–23.6 °C) [ 36 ] and the potential for isolated or regular but transient high temperatures to negatively affect medicines, particularly when considering storage periods of 3–6 months, is disputed [ 15 ]. Indeed, when researchers have assessed all temperatures that medicines have been exposed to over a pre-determined period in the home environment, they have found that the majority of patients store their medicines in acceptable temperature conditions (both studies looking at medicines which needed to be stored either below 25 or 30 °C) [ 37 , 38 ]. As medicines which are sensitive to humidity are stored in protective packaging, it is temperature that remains the primary storage concern when considering medicines reuse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have identified that the majority of patients properly store their medications at room temperature. 22,23 However, those with refrigerated medications often required additional education on correct storage requirements. 24,25 To ensure that the medications are safe during patient donation, delegates from the drug repository programs or facilities should consider asking additional questions to ensure compliance with the drug's label.…”
Section: Drug Donations In An Open Systemmentioning
confidence: 99%